PENGARUH INOVASI, TEKNOLOGI INFORMASI, DAN ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA USAHA - Fufung Alfu Lailah; Tjiptogoro Dinarjo Soehari (Akademika : Jurnal Teknologi Pendidikan, 2020)
This study aims to obtain information about the effect of entrepreneurial orientation on innovation, information technology on innovation, entrepreneurial orientation on business performance, information technology on business performance, innovation on business performance, innovation mediates the effect of entrepreneurial orientation on business performance and innovation mediates the effect of information technology on business performance of business shop owners in Glodok Market. The data used are primary data derived from questionnaires distributed to respondents. The population in this study were all business shop owners in Glodok Market is 758 with a probability sampling technique of 176 stores as respondents. The analytical method used is structural equation modeling (SEM) using the Lisrel 8.80 program. The results showed that there was no effect of entrepreneurial orientation on innovation, there was a positive and significant effect on entrepreneurial orientation on business performance, there was a positive and significant influence on information technology on innovation, there was a positive and significant effect on information technology on business performance, there was a positive and significant effect on innovation on business performance, innovation cannot mediate entrepreneurial orientation to business performance and innovation can mediate information technology on business performance.